Análisis de la eficiencia del control de un motor asincrónico mediante SVPWM en lazo abierto - Sánchez Gamboa, Franklin Israel (2022)
Space vector pulse width modulation (SVPWM) control is a technique frequently used within the industry, but there is little information about the efficiency of the controller when performing this method. This research aims to analyze the efficiency of the controller of an asynchronous motor, using space vector pulse width modulation (SVPWM) in open loop. In operating conditions with a constant torque of 1.5 Newton per meter varying the speed. It is carried out by applying the mathematical model, the formulas of commutation times and space vectors in an algorithm in Simulink-Matlab taking into account the maximum and minimum values of operation applying the space vector pulse width modulation method for generate the trigger signal in the Insulated Gate Bipolar Transistor (IGBT's) bridge, implementing the model in the Lucas Nulle practice module taking the power data and calculating the efficiency to compare with the mathematical model and validate, resulting that the efficiency of the control module varies according to the switching speed of the semiconductor block, with the operation of a motor of 0.37kW and 1KW at a speed of 200rpm, the efficiency of the controller reaches a value of 72.67% in the physical model that consists of 6 IGBT's of 1 kVA and 69% in the simulated model, presenting an error of 5% and a switching speed of the IGBTs of 248.641ms.